FORMULATION, OPTIMIZATION, AND CHARACTERIZATION OF A THERMOSENSITIVE IN SITU NASAL GEL INCORPORATING CHITOSAN NANOPARTICLES OF ZOLMITRIPTAN FOR THE MANAGEMENT OF ACUTE MIGRAINE ATTACKS - Rohini Karunakaran,; Sujith S Nair,; Pankaj Mohan Pimpalshende,; Diksha Devi,; Kanika,; Kajal Sachan,; Yash Srivastav,; S. Bhama, (The Bioscan, 2025)
The current study concentrated on creating and refining a zolmitriptan in situ thermosensitive nasal gel with chitosan nanoparticles for improved migraine treatment. Sodium tripolyphosphate (TPP) was used as the cross-linking agent in the ionic gelation process to create chitosan nanoparticles. To make a formulation that changes from sol to gel at nasal cavity temperature, the nanoparticle suspension was mixed with a gel matrix that contained Poloxamer 407 and Poloxamer 188. Particle size, zeta potential, mucoadhesive strength, gelation temperature, viscosity, gel strength, and in vitro drug release were all assessed for a number of formulations (TSGF1–TSGF7). Among the formulations, TSGF3 was identified as the best optimized due to its ideal gelation temperature (35.45 ± 0.37°C), balanced viscosity (493 cP at 40°C and 3523 cP at 34°C), and satisfactory mucoadhesive strength (3614 ± 14.82 dynes/cm²). The drug release study revealed that TSGF3 provided a sustained release of 90.79% over 420 minutes, indicating its potential for prolonged therapeutic effect. The drug and excipients did not significantly interact, according to FTIR analysis. These findings support that the zolmitriptan-loaded thermosensitive chitosan nanoparticle gel is a promising system for intranasal delivery, offering both rapid onset and sustained migraine relief through improved bioadhesion and controlled drug release.